Mapping Academic and Behavioural Difficulties among At-Risk Students in Indonesian Public Elementary Schools: A School-Based Approach within an RTI Framework - Deden Mulyadi (proceedings.icesy, 2026)
This study aimed to explore learning difficulties among at-risk students in a public primary school by integrating parent and student perspectives, within the framework of Response to Intervention (RTI). A descriptive exploratory design was employed using parent questionnaires (n = 504) and student questionnaires (n = 507) involving Grades 1–6 students in one public primary school in Central Jakarta. The results indicated that most students lived in crowded households, with 64.1% of Grades 1–3 students and 42.6% of Grades 4–6 students living with five family members in one house. Child caregiving was predominantly provided by mothers (61.9% in Grades 1–3 and 64.3% in Grades 4–6). Most Grades 1–3 students reported positive attitudes toward reading (97.1%) and mathematics (96.8%). In contrast, the dominant issue among Grades 4–6 students was difficulty maintaining learning focus (63.1%). These findings highlight the importance of early mapping of at-risk students to strengthen universal prevention and tiered learning support within the RTI framework in public primary schools.